Scientists who changed history - Black, Alexandra (DK Publishing, 2019)
Provides accounts of the most important scientific discoveries throughout history, including Galileo's telescope, Ford's mass production of the automobile, and Bell's invention of the telephone. Chronicles the men and women who have contributed to scientific pursuits and the ages in which they sometimes struggled to bring their innovations into the mainstream. Includes illustrations and sidebars.